The effects of COVID-19 on firms’ liquidity: evidence from the Athens Stock Exchange - Nerantzidis, Michail; Koutoupis, Andreas; Tzeremes, Panayiotis; Drogalas, Georgios; Mitskinis, Dimitrios (Journal of Business Economics and Management, 2023)
Motivated by the recent study of De Vito and Gómez (2020), this paper examines how the COVID-19 pandemic could influence the liquidity of Greek listed firms. It also explores the main factors that drive the level of operating cash flow (OCF). By simulating a decrease of 50% and 75% in sales, we perform stress-tests on three liquidity ratios for 154 listed firms on Athens Stock Exchange considering their degree of flexibility. For these firms, we also investigate if industry sector matters. Finally, OLS and quantile regression analysis is performed to gain a more detailed and complete picture of the determinants of the OCF. The findings show that on average a firm with limited flexibility, in the worst scenario, would consume its cash reserves in about two months. Furthermore, approximately 9% of all firms would become illiquid in about one year, whereas about 12% would become illiquid within two years. It is also observed that liquidity does not significantly variate across sectors. On average, as revealed by OLS method, the findings support that Total Governance, ROA and Female board significantly affect the OCF. The paper enables policymakers to perceive the magnitude of liquidity risk and improve their decision making.